2022
DOI: 10.1007/s10583-022-09481-0
|View full text |Cite
|
Sign up to set email alerts
|

Revamping Mrs. Piggle-Wiggle in Classroom Practice: Negotiating Stereotypes, Literary Language, and Outdated Values

Abstract: In this contribution, we explore something rarely reported on in research on children’s literature: how an old children’s book is re-appropriated and altered in ongoing teaching practice. The material consists of the book used in instruction, a Swedish translation of Mrs. Piggle-Wiggle (Tant Mittiprick), and transcribed audio recordings collected throughout six weeks of teaching. Participants include a librarian, who conducted the lion’s share of the discussions based on the books, two teachers, and two groups… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…Lindqvist's concept is used as the backbone of this paper exploring and promoting creative and child-led interactions with literary texts. In this endeavour, we build on a previous study (Malilang & Walldén, 2022) which identified untapped potentials in read-aloud discussions for further encouraging students' playful expressions and intertextual connections in openended dialogue. To provide empirical grounding, we use data from a different study (Walldén, 2022) in which the participant teacher to a greater extent leveraged such potential.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Lindqvist's concept is used as the backbone of this paper exploring and promoting creative and child-led interactions with literary texts. In this endeavour, we build on a previous study (Malilang & Walldén, 2022) which identified untapped potentials in read-aloud discussions for further encouraging students' playful expressions and intertextual connections in openended dialogue. To provide empirical grounding, we use data from a different study (Walldén, 2022) in which the participant teacher to a greater extent leveraged such potential.…”
Section: Introductionmentioning
confidence: 99%
“…This framework, however, has been criticised as being overly focused on the individual reader (discussed in Degerman & Johansson, 2010). While influential elaborations on reader response theory, such as Langer's (1995Langer's ( /2017 stances on envisionment building and Tengberg's forms of reading (2011), have contributed to understanding potentials for literary understanding in classroom discussions, these approaches still focus on classifying responses (e.g., Economou, 2015;Malilang & Walldén, 2022;Nordberg, 2022;Wilinger, 2022).…”
Section: Introductionmentioning
confidence: 99%